2007
DOI: 10.20870/oeno-one.2007.41.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of both abscisic acid and indol-acetic acid in controlling grape berry ripening process

Abstract: Aims:The objective was to better understand the mechanisms involved in grape ripening that brings about important changes in the physiology and chemistry of the fruit. So we focused on the involvement of two growth regulators: abscisic acid (ABA) and indol-acetic acid (IAA) in controlling grape berry ripening process Methods and results:We described the evolution of the two plant growth regulators during the development of cv. Merlot grapes (Vitis vinifera L.). In order to better understand the role of ABA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
1
25
2
Order By: Relevance
“…In contrast, ethylene is known to stimulate auxin biosynthesis by activating the tryptophan aminotransferases mentioned above (Stepanova et al 2005(Stepanova et al , 2007Swarup et al 2007). Based on auxin application experiments using preveraison grape berries and changes in the concentration of IAA levels during berry development (Inaba et al 1976;Cawthon and Morris 1982;Zhang et al 2003;Deytieux-Belleau et al 2007;Böttcher et al 2010), it has been suggested that low IAA levels are a requirement for the commencement of grape berry ripening (Böttcher et al 2010). It is therefore possible that the AVGand CEPA-induced effects on berry ripening observed in this study were indirectly brought about through changes in auxin levels in the fruit.…”
Section: Avg Can Promote Ripeningmentioning
confidence: 67%
See 2 more Smart Citations
“…In contrast, ethylene is known to stimulate auxin biosynthesis by activating the tryptophan aminotransferases mentioned above (Stepanova et al 2005(Stepanova et al , 2007Swarup et al 2007). Based on auxin application experiments using preveraison grape berries and changes in the concentration of IAA levels during berry development (Inaba et al 1976;Cawthon and Morris 1982;Zhang et al 2003;Deytieux-Belleau et al 2007;Böttcher et al 2010), it has been suggested that low IAA levels are a requirement for the commencement of grape berry ripening (Böttcher et al 2010). It is therefore possible that the AVGand CEPA-induced effects on berry ripening observed in this study were indirectly brought about through changes in auxin levels in the fruit.…”
Section: Avg Can Promote Ripeningmentioning
confidence: 67%
“…Abscisic acid (ABA) levels rise sharply around the time of veraison and the application of ABA during a certain period before veraison can advance the initiation of ripening (Coombe 1973;Coombe and Hale 1973;Hale and Coombe 1974;Inaba et al 1976;Cawthon and Morris 1982;Davies et al 1997;Zhang et al 2003;Deytieux-Belleau et al 2007;Wheeler et al 2009). In addition, some of the genes expressed during the ripening phase are likely to be ABAresponsive Grimplet et al 2007;Pilati et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence in the network of transcripts encoding an auxin-responsive protein (TC56885) and an indole-3-acetic-acid 14 transcription factor (TC70800) suggests a role for auxin signaling in the repression of ripening (Davies and Bottcher, 2009). Auxin levels are high during berry formation, and auxin treatment delays berry ripening (Deytieux-Belleau et al, 2007;Davies and Bottcher, 2009). Figure 6 shows the network representing the integrated transcriptome and metabolome data sets, describing the molecular events taking place during ripening and withering (Supplemental Table S2 and Supplemental Data Set S5, respectively).…”
Section: Integration Of Data Sets (Hypothesis-free Approach)mentioning
confidence: 99%
“…Interestingly, the highest levels of auxin are observed at early berry development, then its concentration decreases rapidly before véraison, becoming undetectable after two weeks [6,7]. On the other hand, another study showed no dramatic changes in auxin concentration during berry growth and development [8].…”
Section: Introductionmentioning
confidence: 99%